Multilingualism, Nationhood, and Cultural Identity : Northern Europe, 16th-19th Centuries - Robitaille-Ibbett, Mary; Brandt, Bettina; Sanchez-Summerer, Karene; Kok-Escalle, Marie-Christine, 1948-; Frijhoff, Willem (Book collections on Project MUSE., 2017)
"Multilingualism, nationhood, and cultural identity : northern Europe 16th-19th centuries offers systemic and analytical studies of the little-known multilingual practices of northern Europe before the creation of the nation states. In the 17th century, the Dutch Republic was home to a society where the practice of multilingualism was embedded in its social dynamics, in the use of dialects and foreign languages with their social functions and group identities. These same realities can be found today in other northern European countries. The notion of a national language did not crystallize before the early modern period and the creation of nation states. However, the ideal of a universal language has been present throughout history. This methodological discussion of the systems of European countries where multiple languages coexisted between the 16th and the 19th centuries provides valuable lessons for the understanding of today societies"--Back cover.